Chlamydia pecorum–Associated Sporadic Ovine Abortion. Issue 1 (January 2021) - Westermann, Thomas; Jenkins, Cheryl; Onizawa, Emily; Gestier, Sarah; McNally, Justine; Kirkland, Peter; Zhang, Jing; Bogema, Daniel; Manning, Leah K.; Walker, Keith; Pinczowski, Pedro
Despite previous detection of Chlamydia pecorum in sporadic ovine abortions, published descriptions of naturally occurring infections with fetoplacental lesions are lacking. This report provides the first descriptions of severe necrosuppurative chorionitis with vasculitis, and fetal pyelonephritis and enteritis in late-term abortions of maiden ewes. Chlamydial infection was detected using a Chlamydia genus-specific qPCR (quantitative polymerase chain reaction) on tissue extracts from 3 fetuses. C. pecorum was identified using a targeted qPCR assay, which also determined infectious load within fetal tissues. The presence of viable C. pecorum in fetal samples was confirmed by cell culture. Multilocus sequence typing (MLST) data indicated that the C. pecorum strains from each fetus were identical and of sequence type (ST) 23. Chlamydia sp. immunohistochemistry showed strong positive immunolabeling of fetoplacental lesions. Other infectious abortigenic agents were excluded with specific testing. This report confirms C. pecorum as a likely cause of ovine abortion and provides the first descriptions of associated fetoplacental lesions in naturally infected sheep.